2019
DOI: 10.14238/sp20.4.2018.242-8
|View full text |Cite
|
Sign up to set email alerts
|

Fungsi Ginjal Pasien Thalassemia Mayor yang Mendapatkan Kelasi Besi Oral

Abstract: Latar belakang. Peningkatan angka kelangsungan hidup pasien thalassemia menyebabkan terdeteksinya berbagai penyakit komorbid termasuk komplikasi pada ginjal. Anemia kronis, kelebihan besi, dan pemakaian kelasi besi, terutama kelasi besi oral diduga berpengaruh pada fungsi ginjal. Berbagai derajat disfungsi tubular dan abnormalitas laju filtrasi glomerulus (LFG) dideteksi dengan berbagai macam pemeriksaan. Tujuan. Membandingkan laju filtrasi ginjal (tubulus dan glomerulus) pada pasien thalassemia yang mendapatk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
2
0
5
Order By: Relevance
“…24 Sari et al also reported a decrease in eFLG in patients receiving oral iron chelation therapy. 9 Decreased eGFR can occur due to chronic anemia, iron overload, and the use of certain This electrolyte imbalance can cause muscle weakness, cramps, and heart problems. Glomerular hyperfiltration and decreased eGFR can lead to chronic renal failure, which is a serious and lifethreatening condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Sari et al also reported a decrease in eFLG in patients receiving oral iron chelation therapy. 9 Decreased eGFR can occur due to chronic anemia, iron overload, and the use of certain This electrolyte imbalance can cause muscle weakness, cramps, and heart problems. Glomerular hyperfiltration and decreased eGFR can lead to chronic renal failure, which is a serious and lifethreatening condition.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Clinical studies show varying degrees of tubular dysfunction and glomerular filtration rate abnormalities are common findings in βthalassemia patients. 9 Chronic anemia, iron overload, and the use of iron chelation are thought to be related to the manifestation of kidney disorders. 10 Impaired kidney function can occur without symptoms and before serious manifestations appear, so early markers are needed to detect kidney damage.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia termasuk negara dengan tingkat kejadian talasemia tingg, bukan hanya dilihat dari jumlah pasien, tapi juga dilihat dari frekuensi kelainan gen yang ditemukan. Pada tahun 2018, Rumah Sakit Cipto Mangunkusumo mencatat 666 asien kasus talasemia (Sari et al, 2018).…”
Section: Pendahuluanunclassified
“…Hal ini sejalan dengan penelitian Teny dkk. 5 Peningkatan LFG dapat merupakan gejala awal yang disebut hiperfiltrasi. Hiperfiltrasi dapat mengakibatkan perengangan dinding kapiler dan kerusakan epitel glomerulus sehingga dapat terjadi penurunan LFG yang progresif.…”
Section: Pembahasanunclassified
“…Pada tahun 2018, Rumah Sakit Cipto Mangunkusumo mencatat 666 pasien kasus talasemia. 5 Tingkat kelangsungan hidup pasien talasemia telah meningkat, terutama di negara-negara dengan sumber daya kesehatan yang memadai dan pengobatan yang sesuai. Terapi melalui transfusi darah serta pengendalian zat besi dengan metode tepat waktu telah meningkatkan harapan hidup anak-anak yang mengidap talasemia.…”
unclassified